Church, World and Kingdom: The Eucharistic Foundation of Alexander Schmemanns's Pastoral Theology - Plekon, Michael (Cistercian studies quarterly, 2013)
The article reviews the book "Church, World and Kingdom: The Eucharistic Foundation of Alexander Schmemanns's Pastoral Theology," by William C. Mills.